Albumin-Mediated Size Exclusion Chromatography: The Apparent Molecular Weight of PSMA Radioligands as Novel Parameter to Estimate Their Blood Clearance Kinetics - Jan-Philip Kunert; Sebastian Fischer; Alexander Wurzer; Hans-Jürgen Wester (Pharmaceuticals, 2022)
A meticulously adjusted pharmacokinetic profile and especially fine-tuned blood clearance kinetics are key characteristics of therapeutic radiopharmaceuticals. We, therefore, aimed to develop a method that allowed the estimation of blood clearance kinetics in vitro. For this purpose, 177Lu-labeled PSMA radioligands were subjected to a SEC column with human serum albumin (HSA) dissolved in a mobile phase. The HSA-mediated retention time of each PSMA ligand generated by this novel ‘albumin-mediated size exclusion chromatography’ (AMSEC) was converted to a ligand-specific apparent molecular weight (MWapp), and a normalization accounting for unspecific interactions between individual radioligands and the SEC column matrix was applied. The resulting normalized MWapp,norm. could serve to estimate the blood clearance of renally excreted radioligands by means of their influence on the highly size-selective process of glomerular filtration (GF). Based on the correlation between MW and the glomerular sieving coefficients (GSCs) of a set of plasma proteins, GSCcalc values were calculated to assess the relative differences in the expected GF/blood clearance kinetics in vivo and to select lead candidates among the evaluated radioligands. Significant differences in the MWapp,norm. and GSCcalc values, even for stereoisomers, were found, indicating that AMSEC might be a valuable and high-resolution tool for the preclinical selection of therapeutic lead compounds for clinical translation.